Refugee Matching as a Market Design Application - Tommy Andersson (Lund University, School of Economics and Management, Department of Economics, 2017)
This note contains a few brief remarks on the similarities and differences between some standard market design applications (e.g., kidney exchange and school choice) and the refugee assignment problem. The main conclusion is that the refugee assignment problem is more complex in some dimensions than many of the standard market design applications. Consequently, classical mechanisms cannot be used to solve the problem and more research is needed to, e.g., understand how to model preferences, and how to define relevant axioms and multidimensional constraints.
Keywords: C78; F22; 330; forced migration; asylum seekers; refugee assignment; matching; market design